Mobile-Assisted Language Learning Apps: The Analysis of Duolingo - Muchsinul Khuluq; Mamluatul Hasanah; Muasshomah Muasshomah; Nurul Imamah (Universitas Islam Negeri Palangka Raya, 2024)
The Duolingo application offers foreign language learning, specifically Arabic, to learners worldwide. Although effective, the material within it must meet international language learning standards. This research aims to assess the suitability of Duolingo's material in accordance with the international standards set by ACTFL. This study employs a descriptive qualitative approach, with primary data consisting of Duolingo's materials and secondary data comprising relevant literature. Both data sets are analyzed using Milles and Hubberman's theory. The results indicate that Duolingo complies with the international standards established by ACTFL, covering proficiency levels from Distinguished, Superior, Advanced, Intermediate, to Novice. Each proficiency level ensures that learners can learn a foreign language gradually and systematically according to their language abilities.